Tanggung Jawab Penyedia Layanan Perbankan Terhadap Penyalahgunaan Data Nasabah Berdasarkan Pasal 46 Ayat 1 UU PDP (Kasus Putusan 615/Pdt.G/2023/Pn surabaya) - Arif Rivaldo; Moody R Syailendra (Universitas Ekasakti, 2024)
The relationship between banks and customers is based on two most related elements, namely law and trust. Banks as processors of customer personal data are required to maintain the confidentiality of customer personal data. The government's role in protecting personal data is manifested in the establishment of the Financial Services Authority (OJK) and the ratification of the Personal Data Protection Law (UU PDP), as well as other laws relating to regulations in the banking sector. Regardless of the regulations made by the government and the principles/principles implemented by banking services, cases of personal data leakage still occur. To study this paper, the author used normative legal research with analytical descriptive methods. The author uses secondary data obtained by means of library research to examine some of the documents connected to this writing using a statutory approach, a historical approach and a case approach. The research data discusses the responsibility of banking services for leaking customer data through Decision Case no. 615/Pdt.G/2023/PN Sby.